Petrophysics of fine-grained mass-transport deposits: A critical review. (1st May 2020) - Sun, Qiliang; Alves, Tiago
Graphical abstract: Highlights: Fine-grained MTDs comprise a 'main body' and a 'basal shear zone'. Main body of MTD has contrasting petrophysical properties to their basal shear zone. Main body of MTD tends to be a seal interval, whilst the basal shear zone is fluid carrier. Basal shear zone of MTD can comprise weak layer promoting further slope instability. Abstract: Submarine slope failures and their products occur at variable scales on continental margins and island flanks. Here, we review the petrophysics of fine-grained mass-transport deposits (MTDs) from three representative regions: the Ulleung Basin from offshore Korea, the Ursa Region in the Gulf of Mexico, and the Amazon Fan in the Equatorial Brazil. This study shows that fine-grained MTDs comprise a 'main body' and a 'basal shear zone'. Compared to undeformed 'background' hemipelagic sediments, the main bodies of all studied MTDs are characterised by their: (1) higher resistivity, density, velocity and shear strength, and (2) lower water content, porosity and permeability. These properties indicate that MTDs are more consolidated than 'background' undeformed strata due marked dewatering and shear compaction during their emplacement, thus enhancing the sealing competence of such strata. However, the basal shear zones show contrasting petrophysical trends, recording an increase in porosity when compared to the main MTD bodies. This suggests that the fractured basal shear zones of MTDs serve as main fluid paths, and fluids can accumulate within or laterally migrate along them. This study ends by postulating that dipping strata on continental slopes can likely fail under its own gravity, with fractured, gas-charged basal shear zones at the base of MTDs comprising weak layers for further slope instability.